2012
DOI: 10.3177/jnsv.58.153
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Maintenance of Envelope Integrity in Selenomonas ruminantium: Cadaverine Biosynthesis and Covalent Modification into the Peptidoglycan Play a Major Role

Abstract: Summary Polyamine is a small organic polycation composed of a hydrocarbon backbone with multiple amino groups which ubiquitously exists in all living organisms from bacteria to higher animals. The critical step of polyamine biosynthesis generally includes the amino acid-decarboxylating reaction to produce the primary diamines, such as a synthesis of putrescine (NH 3 ϩ ·(CH 2 ) 4 ·NH 3 ϩ ) from ornithine, and cadaverine (NH 3 ϩ ·(CH 2 ) 5 ·NH 3 ϩ ) from lysine, which are catalyzed by pyridoxal-5 ′ -phosphate (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…This correlates well with the function as an OM tether, as in E. coli Braun's lipoprotein is the most numerous protein in the cell (Braun, 1975). Furthermore, this supports the hypothesis that all Negativicutes utilize OmpM as a form of attachment (Kojima and Kamio, 2012). Moreover, this is consistent with a transcriptomics study of three Veillonella species from the mouth, which found all three copies of OmpM to be the most abundant OM transcripts (Do et al, 2015), further highlighting the importance of these proteins (Kojima et al, 2016).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This correlates well with the function as an OM tether, as in E. coli Braun's lipoprotein is the most numerous protein in the cell (Braun, 1975). Furthermore, this supports the hypothesis that all Negativicutes utilize OmpM as a form of attachment (Kojima and Kamio, 2012). Moreover, this is consistent with a transcriptomics study of three Veillonella species from the mouth, which found all three copies of OmpM to be the most abundant OM transcripts (Do et al, 2015), further highlighting the importance of these proteins (Kojima et al, 2016).…”
Section: Resultssupporting
confidence: 84%
“…OmpM is an alternative method for tethering the OM to the peptidoglycan by binding of polyamine-modified peptidoglycan through an S-Layer homology (SLH) domain and a transmembrane β-barrel for OM attachment (Kojima and Kamio, 2012). This contrasts with Escherichia coli's Braun's lipoprotein (Lpp), which covalently binds PG and integrates into the OM via a lipid moiety (Braun and Rehn, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Selenomonas , another genus of the Negativicutes, appears to be the only genus of Gram‐negatives with no OmpA‐like domain‐containing proteins or Lpp. Selenomonas do, however, have a peptidoglycan modified with the polyamine cadaverine which is bound by an alternative OMP, OmpM (Mep45) by virtue of a SLH (S‐layer homologous) domain (Kojima et al ., ), this connection is important for OM integrity (Kojima et al ., ; Kojima and Kamio, ). No information on OM constriction during cell division in the Negativicutes is currently available.…”
Section: Passive Outer Membrane Constriction By Simple Tethering?mentioning
confidence: 98%
“…Another feature of the diderm Firmicutes envelope that has been studied is the mechanism of OM attachment, completely different from that of E. coli (Kojima et al, 2010). E. coli utilizes Braun's lipoprotein (Lpp) (Braun & Rehn, 1969) and other redundant systems such as Pal (Cascales et al, 2002) and OmpA (Park et al, 2011) for attachment of the OM, whereas Selenomonas ruminantium was shown to bind polyamine-modified peptidoglycan to the OM through a protein that contains an S-Layer homology domain (SLH) and a porin domain (OmpM) (Kojima & Kamio, 2012).…”
Section: Firmi Cute S With An Outer Memb R Ane?mentioning
confidence: 99%